HUBUNGAN PERAN KYAI, PERILAKU PEMILIH DENGAN PILIHAN MASYARAKAT BANJARNEGARA PADA PEMILU GUBERNUR DAN WAKIL GUBERNUR JAWA TENGAH TAHUN 2018 - Wahyu Setiya Aji; Muhammad Adnan (Journal of Politic and Government Studies, 2020)
The regional head election for the 2018-2023 period was followed by 2candidate pairs, Ganjar Pranowo as incumbent paired with Taj Yasin and his rivalwas Sudirman said who was paired with Ida Fauziah. With the presence of 2candidates from NU (Nahdlatul Ulama), this phenomenon is quite interesting, inBanjarnegara District there are 2 large Islamic boarding schools (NU) (NahdlatulUlama) that provide support to different candidates of candidate for governor andcandidate vice governor, in the boarding school kyaiare figures influential indetermining the direction of political support, furthermore the power of kyai is notonly in the islamic boarding schools community, but also in the surroundingcommunity. This study aims to assess the relationship between the role of kyai withthe community choices in Banjarnegara district in 2018 Central Java GovernorElection, and assess the relationship between voter behavior and community choices.This research approach is quantitative correlational, and data are collected by surveytechniques.The conclusion drawn from this study is first, there is a significantrelationship between the role of the kyai and community choice, based on the resultsof statistical tests that have been done it can be seen that the role of the kyai has arelationship with community choices, furthermore the choice of Ganjar Pranowo hasa stronger value compared to the electability of Sudirman-Said Ida Fauziyah. Andsecondly, there is no relationship between voter behavior with the choices of thepeople of Banjarnegara Regency in 2018 Central Java Governor Election.Keywords: Central Java Governor Election, the role of kyai, voting behavior, communitychoices